(untitled) (Applied Biological Research, 2023)
Forty-nine bread wheat (Triticum aestivum L.) genotypes were studied under rainfed conditions at three agroecologically varied locations in South-Western Ethiopia namely, Chena, Masha and Shey Bench, during 2017and 2018 with the objective to estimate their genetic variability, heritability and genetic advance using 7 x 7 simple lattice design. Data were collected for 12 agronomic characters. The analyses of variance revealed highly significant differences (p < 0.01) among wheat genotypes for all the traits studied at these locations, except for the number of t-1 at Chena and biomass yield at Masha wherein genotypes had significant differences only at p < 0.05 level and the number of spikelets spike-1 at Shey Bench wherein genotypes showed non significant difference. The phenotypic coefficients of variation were relatively greater than those of genotypic coefficients of variation for most of the characters studied; however, the magnitudes of differences were relatively high for the number of tillers, number of kernels spike-1, biomass yield and grain yield. High heritability coupled with moderate genetic advance (as % mean) were observed for days to heading, days to maturity, spike length and grain filling period at all these locations. Therefore, any improvement in these characters would result in a substantial increment in grain yield in South-Western Ethiopia which, otherwise, is rich in natural resources but poor in their efficient utilization.